2011
DOI: 10.1556/aphysiol.98.2011.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-methyl-D-aspartate receptor antagonists on D,L-homocysteine thiolactone induced seizures in adult rats

Abstract: The aim of our study was to investigate the effects of ifenprodil and MK-801 on D,L-homocysteine thiolactone induced seizures in adult rats.Male Wistar rats were divided into following groups: 1. Saline-treated (C, n=10); 2. D,L-homocysteine thiolactone 8 mmol/kg, i.p. (H, n=7); 3. Ifenprodil 20 mg/kg i.p. (IF, n=8); 4. MK-801 0.5 mg/kg, i.p. (MK, n=8) and 5. Groups that received IF or MK 30 minutes prior to H (IFH, n=8 and MKH, n=8). Seizure behavior was assessed by incidence, latency, number and intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Previously published study confirms this assertion (Marković et al 2011). Namely, administration of folic acid 30 minutes prior to DL-Hcy TLHC decreased the incidence of seizures and increased latency, as well as mean total spectral power density in EEG recording.…”
Section: R a F Tsupporting
confidence: 61%
“…Previously published study confirms this assertion (Marković et al 2011). Namely, administration of folic acid 30 minutes prior to DL-Hcy TLHC decreased the incidence of seizures and increased latency, as well as mean total spectral power density in EEG recording.…”
Section: R a F Tsupporting
confidence: 61%
“…The majority of seizure episodes in the ifenprodil (72.1%) and MK-801 (73.1%) groups were significantly different compared to the D,L-homocysteine thiolactone treated group (36.0%). Our findings suggest that D,L-homocysteine thiolactone induces seizures through the stimulation of NMDA receptors in the central nervous system but other mechanisms (i.e., NO signalling) may also be involved (58).…”
Section: +mentioning
confidence: 77%
“…Recently, Stanojlović et al 59 showed that acute administration of HCT to adult rats significantly alters neuronal circuits, leading to epileptogenic activity in the EEG with characteristic spikes-and-wave discharges (SWD), and convulsive episodes (manifested through 5grade descriptive rating scale addapted by Stanojlović et al 59 ) in animal behavior. HCT-induced seizures are accepted as a suitable model of generalized epileptic seizures in which coexistence of convulsive and absence-like seizures were proven 60,61 . This is one of the advantages of this particular epilepsy model which allowed reliable investigations of variety seizure activity modifications, like paradoxical sleep deprivation 62 .…”
Section: Nitric Oxide-mediated Neurotransmission In the Central Nervo...mentioning
confidence: 99%